Can the Land Use Master Plan Control Urban Expansion and Protect Farmland in China? A Case Study of Nanjing. (23rd April 2018) - Shao, Zinan; Spit, Tejo; Jin, Zhifeng; Bakker, Martha; Wu, Qun
Abstract: Urbanization represents a challenge for plans aimed at controlling urban expansion and protecting farmland, such as the land use master plan (LUMP) instituted by the Chinese national government. This paper studies the effectiveness of such top–down plans under the authoritarian regime through the case study of Nanjing. In contrast to previous studies that compare actual and planned land‐use maps, we compare actual and planned land‐use patterns. We use land‐use change data to examine spatio‐temporal land‐use change between the years 1997 and 2014. The results indicate that the actual amount of urban‐rural built‐up land exceeded planned regulatory amount by 50, 185 ha and the total farmland was 70, 541 ha less than the target outlined in the LUMP (1997–2010). Based on these results, and the fact that the allowed total urban‐rural built‐up land had already been surpassed in 2014, it is to be expected that the target of farmland protection outlined in the LUMP (2006–2020) will be broken, signaling the ineffectiveness of the plan to control urban expansion and protect farmland. Plan‐led developments (e.g., new towns, development zones) and market forces (e.g., housing market, foreign direct investment) explain these developments. This study indicates that when cities embrace "growth‐led" development and entrepreneurial governance, the ability of plans to control urban expansion and protect farmland is severely limited.